Increase in muscle power is associated with myofibrillar ATPase adaptations during resistance training - Philippe, A. G.; Lionne, C.; Sanchez, A. M. J.; Pagano, A. F.; Candau, R. (Experimental Physiology, 2019)
This study aimed to examine the effects of resistance training on gains in the external mechanical power output developed during climbing and myofibrillar ATPase (m-ATPase) activity in rat. Using rapid flow quench experiments, we show that resistance training increases both the power output and m-ATPase activity in the FDP, biceps and deltoid muscles. Data fitting reveals that theses functional ameliorations are explained by an increase in the rate constant of ATP hydrolysis products liberation and may certainly contribute to performance gains.